2020
DOI: 10.3390/biom10060923
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-Based Medicinal Properties of Stingless Bee Products: Recent Progress and Future Directions

Abstract: Stingless bees are a type of honey producers that commonly live in tropical countries. Their use for honey is being abandoned due to its limited production. However, the recent improvements in stingless bee honey production, particularly in South East Asia, have brought stingless bee products back into the picture. Although there are many stingless bee species that produce a wide spread of products, known since old eras in traditional medicine, the modern medical community is still missing more investigational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 151 publications
1
84
0
9
Order By: Relevance
“…While aging, the aromas from the cerumen are incorporated into honey, giving its intense aroma compared to A. mellifera honey. It has been reported that cerumen extracts have anti-inflammatory and antimicrobial properties [ 49 , 51 , 52 ] and it is possible that the antibiotics and antioxidants from the cerumen are integrated in the honey during aging process [ 50 ]. Report showed that a total of 100 compounds have been identified from stingless bee propolis from 2000 to 2019 by groups in Brazil, South Asia and Australia [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…While aging, the aromas from the cerumen are incorporated into honey, giving its intense aroma compared to A. mellifera honey. It has been reported that cerumen extracts have anti-inflammatory and antimicrobial properties [ 49 , 51 , 52 ] and it is possible that the antibiotics and antioxidants from the cerumen are integrated in the honey during aging process [ 50 ]. Report showed that a total of 100 compounds have been identified from stingless bee propolis from 2000 to 2019 by groups in Brazil, South Asia and Australia [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, flavonoid, together with phenolic compounds, are reported to contribute greatly to biological and pharmacological activities compared to the other propolis constituents [ 6 ], and it is proposed as a good marker of propolis quality [ 7 ]. The nutritionist has highlighted dietary flavonoids as a novel bioactive medicinal agent with various therapeutic properties for human well-being, such as antioxidant, anti-inflammatory, anticancer, and antimicrobial activities [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are different types of honey from various producer bees, the chemical composition of 100 g of the commonly consumed honeys include approximately 64.9–73.1% carbohydrates, 35.6–41.8% fructose, 25.4–28.1% glucose, 16.9–18% water, 1.8–2.7% maltose, 0.23–1.21% sucrose, and 0.50–1% proteins, vitamins, amino acids, and minerals [ 35 ]. Honeys display variability in chemical composition associated with botanical and geographical origin, bee species, and climate [ 36 ]. The majority of the medicinal properties of honeys were associated with their antioxidant phenolic compounds that vary between honeys, typically based on the floral origin of the honey [ 35 ].…”
Section: The Medicinal Properties Of Honeymentioning
confidence: 99%
“…They own this unique role due to their capability to give an electron to free radicals that have unpaired electrons to make them stable and unharmful. ROS, reactive oxygen species; RNS, reactive nitrogen species (adapted from Al-Hatamleh et al, 2020 [ 36 ]).…”
Section: Figurementioning
confidence: 99%